Tradisi Manganan sebagai Media Akulturasi Nilai-Nilai Islam dan Budaya Lokal di Prunggahan Kulon Semanding - Lina Fa’atin Munafa’ah; Candra Agustin; Nurul Hakim (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The manganan tradition in Prunggahan Kulon Village, Semanding District, is a cultural heritage that has been passed down from generation to generation as an expression of community gratitude, particularly before the planting season or after harvest. Its implementation involves several stages, starting from cooperation in preparation for the main activities such as communal prayers and shared meals, which reflect values of togetherness, solidarity, and harmonious social interaction. In addition, this tradition is enriched with local cultural elements and religious practices, such as Javanese chants and collective prayers, creating a sacred atmosphere while strengthening social bonds among community members. Furthermore, the manganan tradition illustrates a process of acculturation between local culture and Islamic values that occurs harmoniously without eliminating the community’s cultural identity. This tradition not only serves as a means of cultural preservation but also functions as a medium for social and religious education, especially for the younger generation. However, its sustainability faces challenges due to modernization and changing lifestyles. Therefore, adaptive preservation efforts are needed through the use of technology, the involvement of community leaders, and integration into educational activities so that the manganan tradition remains sustainable and relevant in contemporary society.   Keywords: Manganan Tradition, Local Wisdom, Islamic Acculturation, Social Values, Cultural Preservation